DESKRIPSI PEMAHAMAN KONSEP SISWA KELAS XI DITINJAU DARI GAYA KOGNITIF - Winda Pratiwi (Almeera Education, 2023)
This is qualitative research. The purpose of the research was to describe students’ conceptual understanding according to their own cognitive styles. The mathematical concept tested on the student was a system of linear equations of two variables. The subject of this research was two students from Grade XI of SMAN 4 Bantaeng. One of the subjects is field independent and the other student is field dependent. The instruments of this research were Group Embedded Figure Test (GEFT), a conceptual understanding written test, and a task-based interview. The analysis technic of this research was a qualitative descriptive analysis. Based on the research data, it was found that students of the field independently satisfy all indicators of conceptual understanding, namely define a concept in verbal and writing; use models, diagrams, or symbols to present a concept; change a representative form to another form; recognize various meaning of a concept; identify properties of a concept and recognize conditions that define it; compare various concepts; estimate; and provide examples and non-examples of a concept. Students of field dependentweres only satisfy seven indicators of conceptual understanding. The only one that was not satisfied by a student of dependent was recognizing various meanings of a concept.